Development of Agricultural Mechanization in China and Its Current Strategic Focus - Sh. Shuqi; W. Jiasheng; W. Dongwei (Сельскохозяйственные машины и технологии, 2019)
China's agricultural machinery development has gone through fi ve stages in its 100-year history: Germination stage of agricultural machinery development (1917-1949), Construction Stage of Modern Agricultural Machinery Industry System in China (1949-1979), System transformation Stage (1980-1995), Market-oriented stage (1996-2003), Rapid development stage (2004-2014). After the 12th Five-Year Plan, China's 13th Five-Year Plan has been going on for three years. Signifi cant Achievements in Agricultural Mechanization has also made in recent 10 years. Although Agricultural Mechanization in China has made considerable progress, there are still great gaps in agricultural mechanization level compared with developed countries. In order to further narrow the gap between China's agricultural mechanization and developed countries, enhance the scientifi c and technological innovation ability of agricultural machinery, strategic focus of agricultural mechanization have been presented in China. The development strategy of "three steps" is defi ned, that is, the strategic objectives of China's agricultural machinery science and technology innovation and agricultural mechanization development to 2025, 2035 and 2050. Two Development Principles which are full process mechanization and Comprehensive mechanization, and from 1.0 to 4.0 of China Agricultural machinery are emphasized in China.